Urinary Bisphenol A Levels and Measures of Obesity: Results from the National Health and Nutrition Examination Survey 2003–2008. (30th May 2012) - Shankar, Anoop; Teppala, Srinivas; Sabanayagam, Charumathi
Abstract : Bisphenol A (BPA) is a widely used chemical. We examined the association between urinary BPA levels and obesity in the National Health and Nutritional Examination Survey (NHANES) 2003–2008. The main outcome of interest was obesity defined as (1) body mass index (BMI) ≥ 30 Kg/m 2 and (2) waist circumference (WC) ≥ 102 cm in men and ≥ 88 cm in women. Urinary BPA levels were examined in quartiles. Overall, we observed a positive association between increasing levels of urinary BPA and both measures of obesity, independent of potential confounding factors including, smoking, alcohol consumption, and serum cholesterol levels. Compared to quartile 1 (referent), the multivariate-adjusted odds ratio (95% confidence interval) associated with quartile 4 for BMI-based obesity was 1.69 (1.30–2.20);P -trend < 0.0001 and for WC-based obesity was 1.59 (1.21–2.09);P -trend = 0.0009. This association between BPA and both measures of obesity was consistently present across gender and race-ethnic groups (allP -trend < 0.05). Elevated levels of urinary BPA are associated with measures of obesity independent of traditional risk factors. This association is consistently present across gender and race-ethnic groups. Future prospective studies are needed to confirm or disprove this finding.